Characterization of Shiga Toxin Subtypes and Virulence Genes in Porcine Shiga Toxin-Producing Escherichia coli - Baranzoni, Gian Marco; Fratamico, Pina M.; Gangiredla, Jayanthi; Patel, Isha; Bagi, Lori K.; Delannoy, Sabine; Fach, Patrick; Boccia, Federica; Anastasio, Aniello; Pepe, Tiziana (Frontiers in Microbiology, 2016)
Similar to ruminants, swine have been shown to be a reservoir for Shiga toxin-producing Escherichia coli (STEC), and pork products have been linked with outbreaks associated with STEC O157 and O111:H-. STEC strains, isolated in a previous study from fecal samples of late-finisher pigs, belonged to a total of 56 serotypes, including O15:H27, O91:H14, and other serogroups previously associated with human illness. The isolates were tested by polymerase chain reaction (PCR) and a high-throughput real-time PCR system to determine the Shiga toxin (Stx) subtype and virulence-associated and putative virulence-associated genes they carried. Select STEC strains were further analyzed using a Minimal Signature E. coli Array Strip. As expected, stx2e (81%) was the most common Stx variant, followed by stx1a (14%), stx2d (3%), and stx1c (1%). The STEC serogroups that carried stx2d were O15:H27, O159:H16 and O159:H-. Similar to stx2a and stx2c, the stx2d variant is associated with development of hemorrhagic colitis and hemolytic uremic syndrome, and reports on the presence of this variant in STEC strains isolated from swine are lacking. Moreover, the genes encoding heat stable toxin (estIa) and enteroaggregative E. coli heat stable enterotoxin-1 (astA) were commonly found in 50 and 44% of isolates, respectively. The hemolysin genes, hlyA and ehxA, were both detected in 7% of the swine STEC strains. Although the eae gene was not found, other genes involved in host cell adhesion, including lpfAO113 and paa were detected in more than 50% of swine STEC strains, and a number of strains also carried iha, lpfAO26, lpfAO157, fedA, orfA, and orfB. The present work provides new insights on the distribution of virulence factors among swine STEC strains and shows that swine may carry Stx1a-, Stx2e-, or Stx2d-producing E. coli with virulence gene profiles associated with human infections.